Immunocytochemical studies of endothelial cells in vivo. I. The presence of desmin only, or of desmin plus vimentin, or vimentin only, in the endothelial cells of different capillaries of the adult chicken (The Rockefeller University Press, 1986)
It is currently believed that the intermediate filaments of endothelial cells contain vimentin subunits exclusively. This inference, however, is derived from studies of only a few types of endothelial cells. By double indirect immunofluorescence and immunoelectron microscopy, we have now examined the endothelial cells of the micro- and macrovasculature of a variety of tissues and organs of adult chicken in vivo for their content of desmin and vimentin. Endothelial cells of the peritubular capillary in the renal cortex, the hepatic sinusoid, and the splenic sinusoid were found to contain only desmin; those of the exocrine pancreas capillary contained both desmin and vimentin; and the endothelial cells of the macrovasculatures and of all the other microvasculatures examined, including the vasa recta of the renal medulla, contained only vimentin. Such heterogeneity suggests that different types of adult chicken endothelial cells may have different embryological origins. To the extent that desmin and vimentin intermediate filaments may be functionally distinct, these results also suggest that different capillary endothelial cells may have different functional properties.